The Effect of Green Trust, Brand Image and Product Knowledge on Purchase Decision with Green Price as Moderating Variable (Study of The Body Shop consumers in Indonesia) - Meliyana Rizki Prabaningrum; Pramono Hari Adi; Weni Novandari; Monica Rosiana (Dinasti Review, 2025)
This research is a type of quantitative research on The Body Shop. This study takes the title